Afghanistan: The Lag of the Cold War - Cordovez, Diego (2016)
The author explains the evolution of events in Afghanistan since 1973 and considers that the Taliban regime and the support and hospitality that it has given to the Al Qaeda organization of Osama Bin Laden constitute, in essence, a left-over, or an epilogue, of the cold war. AIso discussed are current efforts to establish a government in Afghanistan that would ensure stability and peace to a people that has suffered too much over almost three decades as well as some of the possible motives for the terrorist attack against the United States.